1997
DOI: 10.1063/1.364090
|View full text |Cite
|
Sign up to set email alerts
|

A general property of endoreversible thermal engines

Abstract: In this work we propose that endoreversible Carnot–type heat engines have a general property independent of the heat transfer law used to describe heat exchanges between the working fluid and its thermal reservoirs. This property has to do with the so-called ecological function [F. Angulo–Brown, J. Appl. Phys. 69, 7465 (1991)]. According to this property, the efficiency at the maximum of the ecological function is the semisum of the Carnot and the maximum power efficiencies for any heat transfer law. This resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 23 publications
3
86
0
3
Order By: Relevance
“…Now, we define two additional objective functions, one in terms of the so-called modified ecological function (E ≡ W− ∈ T L σ, with σ the rate of total entropy production of the Novikov model and ∈ a parameter which depends on the heat transfer law used in the Novikov model [19,20]). This function is a slight modification of the former ecological function [19], which preserves the original physical meaning of that function; that is, it represents a good trade-off between high power output and low dissipation.…”
Section: Thermoeconomic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Now, we define two additional objective functions, one in terms of the so-called modified ecological function (E ≡ W− ∈ T L σ, with σ the rate of total entropy production of the Novikov model and ∈ a parameter which depends on the heat transfer law used in the Novikov model [19,20]). This function is a slight modification of the former ecological function [19], which preserves the original physical meaning of that function; that is, it represents a good trade-off between high power output and low dissipation.…”
Section: Thermoeconomic Analysismentioning
confidence: 99%
“…Here, De Vos refers to the power production rate W of the Novikov plant model. Later, Barranco-Jiménez and Angulo-Brown [17,18] extended the De Vos thermoeconomic approach, but using the so-called ecological function [19,20], and they also showed that the economical efficiency under this regime of performance lies between the CA efficiency and the Carnot efficiency. In 2009, Barranco-Jiménez [21] studied the thermoeconomics of a nonendoreversible Novikov engine.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Yan [31] proposed that it might be more convenient to use E = P − T 0 σ, if the cold reservoir temperature T L is not equal to the environmental temperature T 0 , from the exergy analysis point of view. Ecological function shows two important properties [6,23,25]. Firstly, if a CA engine works in this regime, the thermal efficiency is shown as…”
Section: Ecological Function Criterionmentioning
confidence: 99%
“…Secondly, in this regime the CA engine produces around 80% of maximum power, while entropy production is reduced down to around 30% of the entropy produced in the maximum power regime. It has been shown that Equation (21), called the semi-sum property, is independent of the heat transfer law used in the process and is termed as a universal property for the endoreversible systems [6,23].…”
Section: Ecological Function Criterionmentioning
confidence: 99%
See 1 more Smart Citation